2017
DOI: 10.1128/jb.00383-17
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations to a Loss-of-Function Mutation in the Betaproteobacterium Aromatoleum aromaticum: Recruitment of Alternative Enzymes for Anaerobic Phenylalanine Degradation

Abstract: Anaerobic phenylalanine (Phe) degradation in the betaproteobacterium involves transamination and decarboxylation to phenylacetaldehyde, followed by oxidation to phenylacetate. The latter reaction is catalyzed simultaneously by two enzymes, a highly specific phenylacetaldehyde dehydrogenase (PDH) and a rather unspecific tungsten-dependent aldehyde oxidoreductase (AOR). Attempting to establish increased synthesis of AOR, we constructed a mutant lacking the gene for PDH. This mutant still grew on phenylalanine, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…A. aromaticum EbN1 is known to grow with the aromatic amino acids Phe and Tyr as sole substrates (16), but growth on related amines has not been tested so far. We observed that this organism also grows very well on the primary aromatic amines benzylamine (BAm) and 2-phenylethylamine (2-PEA) under nitrate-reducing conditions, reaching an optimal growth rate of 0.11 h Ϫ1 , which is equal to that observed with Phe (20). In contrast, no growth was detected with one of the secondary amines (R)-and (S)-1phenylethylamine as the substrate.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…A. aromaticum EbN1 is known to grow with the aromatic amino acids Phe and Tyr as sole substrates (16), but growth on related amines has not been tested so far. We observed that this organism also grows very well on the primary aromatic amines benzylamine (BAm) and 2-phenylethylamine (2-PEA) under nitrate-reducing conditions, reaching an optimal growth rate of 0.11 h Ϫ1 , which is equal to that observed with Phe (20). In contrast, no growth was detected with one of the secondary amines (R)-and (S)-1phenylethylamine as the substrate.…”
Section: Resultsmentioning
confidence: 86%
“…Further degradation pathways of aromatic amines. In analogy to Phe or benzyl alcohol degradation in A. aromaticum EbN1 (20,21), we expected that the aldehydes generated by the amine dehydrogenases are further oxidized by aldehyde dehydrogenases or a tungsten-containing aldehyde oxidoreductase (AOR). Cells grown with 2-PEA or Phe, but not with other substrates, indeed contained a highly specific phenylacetaldehyde dehydrogenase (PDH) using NAD or NADP as electron acceptors with a characteristic ratio of activities of 0.56, as described in reference 22 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations